Hermafroditismo simultáneo y extensión de ámbito de Ctenodrilus serratus (Polyehaeta: Ctenodrllidae) en Baja California Sur, Mexico - Bastida-Zavala, José Rolando (Universidad de Costa Rica, 1994)
This is the first record of simultaneous hermaphroditism in the polychaete Ctenodrilus serratus and of its occurrence in coastal waters of Baja California Sur. A total of 37 specimens were collected from the major spines of five slate-pencil sea urchins, Eucidaris thouarsii, in the subtidal area of a petroleum pier, in Babia de La Paz. Morphological variation is not as high as would be expected in a species complex, but with this report the number of reproductive modes for the species is increassed to three: asexual, protandric and simultaneous hermaphroditism